A general self-template-etched solution route for the synthesis of 2D γ-manganese sulfide nanoplates and their enhanced supercapacitive performance. (8th February 2019) - Li, Deli; Song, Shuang; Lu, Jiaxue; Liang, Jun; Zhang, Yingying; Li, Li
Abstract : Electrode materials with two-dimensional (2-D) structures have attracted tremendous attention because they can exhibit many excellent electrochemical and chemical properties. Abstract : Electrode materials with two-dimensional (2-D) structures have attracted tremendous attention because they can exhibit many excellent electrochemical and chemical properties. Herein, we present a simple and general self-template-etched solution route to fabricate 2-D γ-manganese sulfide (γ-MnS) nanoplates using Mn3 [Fe(CN)6 ]2 as a sacrificial template and Mn source. Detailed analysis and experimental results indicate that the ethylene glycol/H2 O-assisted hydrothermal system and the unique metal frameworks are vitally important for the formation, structure, and morphology of plate-shaped γ-MnS during the sulfidation process. By controlling the growth and etching process, a possible growth mechanism was proposed to interpret the formation of 2D γ-MnS nanoplates. As a promising anode material for pseudocapacitors, the γ-MnS nanoplate sample not only delivers a good specific capacity of 378 F g −1 at 0.2 A g −1 and high rate capability in neutral solution, but it also displays an excellent stable performance, with only about 10% loss after continuous charge–discharge cycling for 4000 cycles at 1.0 A g −1 . The method appears to be a new way for using the sulfuration transformation matrix to obtain other two-dimensional transition metal compounds.